Attitudes and Family Support of the Barrang Caddi Island Community Related to the Utilization of Hypertension Services in Achieving Minimum Service Standards (SPM) - St. Rosmanely; Nasrah; M. Nabil Sakti Pahruddin; Yuana Wira Dwi Satya Ilham Putra; Eva Arista (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Based on Makassar City health profile data in 2021, several aspects of health services and health management still have not achieved the SPM targets for Health and SDG's. At the Barrang Lompoa Community Health Center, only 46.2% of patients suffering from hypertension received health services in 2021, far from the target set at 100%. Objective: To understand the correlation between individual attitudes and family support towards the use of hypertension services at Pustu Barrang Caddi in 2024. Method: The type of research used is Cross Sectional Study. This research was conducted on Barrang Caddi Island, Makassar City in March - April 2024. The population in this study was 351 households. The sample in this study was part of the population on Barrang Caddi Island, that is 188 households. Result: The results of data analysis include univariate analysis with frequency distribution and bivariate chi-square test. Data analysis was carried out bivariate using the Chi-Square test with a significance level of 5% (?=0.05). influence between attitude (p=0.000), family support (p=0.000). From the results of the Chi-Square test, a relationship was found between attitudes and family support on the use of hypertension services at Pustu Barrang Caddi in 2024. Conclusion: There is a relationship between attitudes and family support on the use of hypertension services at Pustu Barrang Caddi in 2024.